Identificação de região de defeito em redes elétricas de distribuição por meio do processamento de alarmes do sistema de supervisão, controle e aquisição de dados - Oliveira, Paulo Henrique Engelmann de (2022)
The electricity distribution system is an economic indicator, and its quality and continuity are an important factor. At the same time, networks are constantly evolving to improve their functionality, clear examples of this are intelligent electrical networks and distributed generation, together with technical indicators that are more demanding. The energy distributors in Brazil are looking to include new and more equipment to identify the condition of the network, such as the insertion of more remote controlled reclosers. The inclusion of these features together with a number of remotely controlled equipment requires an operating methodology that poses challenges and opportunities, sometimes requiring computer support for a better service. In this sense, this work aims to evaluate and present logics for grouping information from remote-controlled equipment in the distribution network and identifying the faulty network sections and indicating maneuvers. For the development of the logics, the methodology of evaluation of the correlations of the information coming from the remote-controlled equipment used, applying combinational and sequential logics. As a differential, the sampling window method is used to ensure that all equipment information is present to present the result. To validate the proposed methodology, case studies of real networks are considered, where the grouping logics were applied. The results found showed the effectiveness of the method, finding solutions as planned and evaluating it in the field. The application of grouping logic provides an improvement in the visualization of events, facilitating actions by the operator, even in switched networks, using field information.